3D Printed Skin‐Interfaced UV‐Visible Hybrid Photodetectors. Issue 25 (11th July 2022) - Ouyang, Xia; Su, Ruitao; Ng, Daniel Wai Hou; Han, Guebum; Pearson, David R.; McAlpine, Michael C.
Abstract: Photodetectors that are intimately interfaced with human skin and measure real‐time optical irradiance are appealing in the medical profiling of photosensitive diseases. Developing compliant devices for this purpose requires the fabrication of photodetectors with ultraviolet (UV)‐enhanced broadband photoresponse and high mechanical flexibility, to ensure precise irradiance measurements across the spectral band critical to dermatological health when directly applied onto curved skin surfaces. Here, a fully 3D printed flexible UV‐visible photodetector array is reported that incorporates a hybrid organic‐inorganic material system and is integrated with a custom‐built portable console to continuously monitor broadband irradiance in‐situ. The active materials are formulated by doping polymeric photoactive materials with zinc oxide nanoparticles in order to improve the UV photoresponse and trigger a photomultiplication (PM) effect. The ability of a stand‐alone skin‐interfaced light intensity monitoring system to detect natural irradiance within the wavelength range of 310–650 nm for nearly 24 h is demonstrated. Abstract : A flexible UV‐vis photodetector array that incorporates a hybrid organic‐inorganic material system is fully 3D printed. The hybrid active material enables a photoresponse in the UV region and triggers a photomultiplication (PM) effect. The printed device is integrated with a console and functions as a stand‐alone skin‐interfaced light intensity monitoring system, which has potential for the medical profiling of photosensitive cutaneous diseases.